Efficacy, accumulation, and transcriptional profile of anti-HIV shRNAs expressed from human U6, 7SK, and H1 promoters - Ryan P. Goguen; Olivier Del Corpo; Camille M.G. Malard; Aïcha Daher; Sergio P. Alpuche-Lazcano; Michelle J. Chen; Robert J. Scarborough; Anne Gatignol (Elsevier, 2021)
The expression of short hairpin RNAs (shRNAs) in cells has many potential therapeutic applications, including as a functional cure for HIV. The RNA polymerase III promoters H1, 7SK, and U6 have all been used to express shRNAs. However, there have been no direct and simultaneous comparisons of shRNA potency, expression level, and transcriptional profile between the promoters. We show that the 7SK and U6 promoters result in higher shRNA levels and potency compared to the H1 promoter but that in transduced T lymphocytes, higher expression levels can also lead to growth defects. We present evidence that Dicer cleavage of shRNAs is measured from the first base pair in the shRNA stem, rather than from the 5' end as previously shown for structurally related microRNAs. As a result, guide-strand identity was unaffected by variations in 5' transcription start sites among the different promoters, making expression levels the main determinant of shRNA potency. While all promoters generated shRNAs with variable start sites, the U6 promoter was the most accurate in using its intended +1 position. Our results have implications for the development of therapeutic small RNAs for gene therapy and for our understanding of how shRNAs are processed in cells.